2001
DOI: 10.1086/318861
|View full text |Cite
|
Sign up to set email alerts
|

Decaying Cold Dark Matter Model and Small-Scale Power

Abstract: The canonical cosmological constant-dominated cold dark matter model (LCDM) may possess too much power on small scales at , manifested as central overconcentration of dark matter and overabundance of dwarf z p 0 galaxies. We suggest an alternative model, LDCDM, where one-half of the cold dark matter particles decay into relativistic particles by . The model successfully lowers the concentration of dark matter in dwarf galaxies z p 0 as well as in large galaxies like our own at low redshift while simultaneously… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 52 publications
2
135
0
Order By: Relevance
“…interactions between cosmological fluids. On the other hand, this kind of interactions is broadly used in cosmology, with the coupling between inflaton and radiation during reheating (e.g., [20]) or the one between dark matter and dark energy (e.g., [8,21,22]), or even the decay of heavy matter particles like WIMPS into light relativistic particles (e.g., [23]). Modern cosmology make strong use of coupled fluids for a variety of purposes, therefore making this study of coupled models in terms of Lotka-Volterra systems of first heuristic interest.…”
Section: Cooperation In the Jungle Universes A General Dynamics mentioning
confidence: 99%
“…interactions between cosmological fluids. On the other hand, this kind of interactions is broadly used in cosmology, with the coupling between inflaton and radiation during reheating (e.g., [20]) or the one between dark matter and dark energy (e.g., [8,21,22]), or even the decay of heavy matter particles like WIMPS into light relativistic particles (e.g., [23]). Modern cosmology make strong use of coupled fluids for a variety of purposes, therefore making this study of coupled models in terms of Lotka-Volterra systems of first heuristic interest.…”
Section: Cooperation In the Jungle Universes A General Dynamics mentioning
confidence: 99%
“…This appears to be contradicted by some observations that indicate an almost constant density core rather than a cusp, both on galaxy scales (e.g., Dalcanton & Bernstein 2000;Salucci & Burkert 2000;de Blok et al 2001) and on cluster scales (Tyson, Kochanski, & dell'Antonio 1998), although the interpretation of these results is controversial (e.g., Broadhurst et al 2000;Shapiro & Iliev 2000;Czoske et al 2002). This has led to suggestions that the dark matter properties may deviate from standard CDM; e.g., the dark matter could be warm (Colín, Avila-Reese, & Valenzuela 2000;Sommer-Larsen & Dolgov 2001), repulsive (Goodman 2000), fluid (Peebles 2000), fuzzy (Hu, Barkana, & Gruzinov 2000), decaying (Cen 2001), annihilating (Kaplinghat, Knox, & Turner 2000), self-interacting (Spergel & Steinhardt 2000;Yoshida et al 2000, Davé et al 2001), or both warm and self-interacting (Hannestad & Scherrer 2000). Alternatively, it has been suggested that stellar feedback from the first generation of stars formed in galaxies was so efficient that the remaining gas was expelled on a timescale comparable to, or less than, the local dynamical timescale.…”
mentioning
confidence: 99%
“…Undoubtedly a large variety of models arise both from different quintessence potentials as well as from different dissipative processes in dark matter. The only requirement is that the potential has the exponential tail (19), or equivalently that the viscosity coefficient has the asymptotic behavior (14). This diversity of possibilities makes the transition period of the universe from its nearly thermodynamical equilibrium early stage towards the superattractor regime model dependent and requires more detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of this problem would imply that structure formation is somehow suppressed on small scales. Several scenarios addressing this issue have been considered assuming some kind of interaction for dark matter particles: non-thermaly produced and weakly interacting [15]; self-interacting [16]; repulsive [17]; annihilating [18] and decaying [19]. It is quite reasonable to expect that dark matter is out of thermodynamical equilibrium and these same interactions are at the origin of the cosmological dissipative pressure.…”
Section: Introductionmentioning
confidence: 99%